Delayed complications after myocardial contusion. Issue 11 (November 1992) - Grech, E D; Dodds, P A; Perry, R A
Abstract : A 45 year old farmer was kicked in the chest by a horse. In the days following the injury episodic breathlessness developed and he was admitted to hospital with right ventricular failure and pulmonary emboli. Echocardiography showed global right ventricular dysfunction but a right ventricular mural thrombus, the likely source of the pulmonary emboli, was not seen. He gradually recovered after treatment with anticoagulant. One month later he presented with a further complication—complete atrioventricular dissociation—that required a dual chamber pacemaker implantation. This patient had few initial manifestations of right ventricular myocardial contusion and this case illustrates that such patients should be closely monitored for delayed complications.